Robust speaker localization using a microphone array - Strobel, Nina; Rabenstein, Rudolf (2000 10th European Signal Processing Conference, EUSIPCO 2000, 2000)
This paper presents a speaker localization system using a microphone array. The array is operated as a steered filter-and-sum beamformer implemented as a summed correlator. In particular, we emphasize the use of a speech pause detector to improve the robustness of the speaker localization system by avoiding erroneous position estimates when no speech signal is present. Simulation results and measurements show that speech pause detection improves the overall system performance considerably.